Analysis of Nutrition Intake Calorie Requirements on The Performance of Futsal Athletes of Students of State University of Makassar Sports Science Study Program Class B 2022 - Faiz, Faiz; Hakim, Arif; Setiawan, Muhammad Arief (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of nutritional intake on the performance of futsal athletes of Makassar State University class B class 2022. Futsal activities require prime physical condition, which is influenced by proper nutritional intake. This study uses a quantitative method with a descriptive approach and experimental design, as well as data collection through the Fat Secret application and BMR Calculator to calculate the nutritional intake of athletes. The subjects of the study were 10 active futsal athletes who underwent regular training programs and rest patterns. The results showed that 6 out of 10 athletes experienced a lack of daily calorie intake, which had an impact on their performance in training and matches. Factors causing this calorie deficiency include the economic and environmental limitations of students. Based on these results, it is recommended that athletes be more disciplined in maintaining a balanced and nutritious diet, and receive better education from coaches and universities regarding the importance of nutritional management. Further research is needed to explore other factors that may affect the performance of futsal athletes.